PENGARUH KETERSEDIAAN ANGGARAN DAN JIWA KEWIRAUSAHAAN TERHADAP KINERJA PELAYANAN APARATUR SKPD DI KABUPATEN ACEH UTARA - Idris, Amiruddin (JURNAL KEBANGSAAN, 2013)
As to this watchfulness aim is to gets description about phenomenon supported by empirical proof and has been found clarity with conclusion about influence from the budget availability and Entrepreneurship towards performance civil servants service SKPD At North Aceh. This research is supposed can give contribution for order government governance and performance civil servants. This research is supposed can give contribution for organization theory development and management theory HRD, especially about order government governance and performance civil servants. Watchfulness uses technique proporsionale stratistified random sampling, with sample total as much as 60 respondents. As to analysis method used, using verification method. While analysis used to be path analysis. Watchfulness result shows quantity direct influence total and not direct from from variable: the budget availability and Entrepreneurship towards performance civil servants service area at North Aceh as big as 39,35 percents. Keyword: the budget availability, Entrepreneurship, performance civil servants.